Speech by Brig. Gen. Dato' Prof. Dr Kamarudin Hussin Vice Chancellor of UniMAP for Opening Ceremony ICOMMS-ICADME Joint Conference 2009 - Kamarudin, Hussin, Brig. Gen Dato’ Prof. Dr (Universiti Malaysia Perlis, 2010)
Event held at Bayview Beach Resort, Penang